ANALISIS BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP PENANAMAN MODAL ASING DI PROVINSI BALI : ANALISIS PARTIAL ADJUSTMENT MODEL - Putu Krisna Adwitya Sanjaya; I Gusti Ayu Wimba; I Gede Putu Kawiana (KRISNA: Kumpulan Riset Akuntansi, 2019)
The urgency of this research is based on the phenomenon of foreign investment which is currently criticized by development theorists and practitioners, in which efforts for a take-off needs capitalization in the form of savings. This is primarily intended to create investment and accelerate economic growth as well. This research aims at revealing influences of United States dollar exchange rate, regional autonomy, and foreign investment of the previous year to foreign investment in Bali simultaneously and partially. This research uses the time series data of the period of 1993 – 2017 by applying dynamic econometrics analysis model of partial adjustment model. This study concludes that US dollar exchange rate, regional autonomy, and previous year’s foreign investment have simultaneously influenced foreign investment. US dollar exchange rate does not significantly influence foreign investment, while regional autonomy and previous year’s foreign investment have positively and significantly influenced the foreign investment. Regional government, therefore, should take real policies on solving the problems of foreign investment. In formulating the policy for the upcoming years, it is important to take exchange rate, regional autonomy, and previous year’s foreign investment into account as real indicators influencing foreign investment in Bali. The foreign investment increase should be achieved in order to be absorbed in all sectors for accelerating economic and development growth in Bali. Keywords: Foreign investment; partial adjustment model; regional autonomy; US dollar exchange rate